MENINGKATKAN PROFESIONALITAS CALON GURU MELALUI PRAKTIK PENGALAMAN LAPANGAN (PPL): STUDI KASUS DI SMK SINAR SENTOSA - Sinaga, Nenni Triana; Silitonga, Amswar; Simarmata, Juliana; Simarmata, Eno; Habeahan, Tison (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The Field Experience Practice Program (PPL) is integral to prospective teacher education to improve professional and pedagogical skills. This report documents the implementation of PPL at Sinar Sentosa Vocational School, Medan, which took place from 12 August to 30 September 2024. This activity includes observation, teaching practice, and additional activities such as school administration and evaluation with tutor teachers. The activity results show that students can apply learning theory to real practice, including classroom management, use of learning media, and interaction with students. However, several obstacles were found, both internally, such as mastering language and managing emotions, and externally, such as the diverse characteristics of students and limited school facilities. This obstacle was overcome through consultation with tutors, group discussions, and creative approaches to learning. This PPL provides valuable experience in forming prospective teachers who not only understand the material but are also able to manage the class effectively and build positive relationships with students. With support from all elements of the school, this program succeeded in increasing students' pedagogical competence and made a real contribution to improving the quality of education.